DIVERSITY OF SEED GERMINATION IN XYLOCARPUS SPECIES - SK. BABU SAHEB; I. VEERA KISHORE; K. BABU; G. ROSAIAH; K. MALLIKARJUNA (International Journal of Pharma and Bio Sciences, 2015)
Xylocarpus species of mangroves are present in coastal areas of the World including India. The Xylocarpus granatum is distributed in very few numbers in coastal areas of Krishna and Godavari regions. On the other hand Xylocarpus moluccensis is distributed in high number in the above regions. The mangrove forest distribution is effected by many factors, including excessive wood gathering, fish pond operations, diversion of fresh water and coastal development-ports, industries etc. As there is vast variation in the distribution of Xylocarpus granatum and Xylocarpus moluccensis in the above regions. We tried to understand the possible causes for narrow distribution of Xylocarpus granatum. As it is known that seed germination, dormancy and dispersal, and other environmental factors play a vital role in the distribution and establishment of these species. Basing on the above speculation, we performed experiments to find out whether there are any innate differences in seed biology of Xylocarpus species. We considered three important factors for seedling establishment of Xylocarpus granatum such as water levels of the tide, seed size and position of the seed in the soil. The results of Xylocarpus granatum showed that the low water level (3-2 cm) resulted in high root length (5.2 cm) when compared to other water levels and large size of seeds formed a large number of roots and radical side of the seed should be intact with soil for root initiation. Whereas, Xylocarpus moluccensis not shown this criteria. Our results indicated that there are differences in the response to water levels of tide, seed size and position of seed in the soil among two species of Xylocarpus. Differences in the germination pattern among two species also reflected in photosynthetic performance of plants. Above data indicates that innate genetic potential of Xylocarpus moluccensis may be contributing to their distributional success. It also indicates that root formation and elongation are crucial for establishment of seedling in Xylocarpus granatum species which could be a reason for its narrow distribution.